Polymer modified asphalt waterproof material and preparation method thereof

By mixing the raw material components and preparation methods of polymer modified asphalt waterproof materials, the problems of aging, embrittlement and cracking of traditional asphalt waterproof materials in the natural environment are solved, significantly extending the service life and reducing maintenance costs, and achieving efficient weather resistance improvement.

CN119529557APending Publication Date: 2025-02-28王玉刚
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411829849.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional asphalt waterproof materials are prone to aging, embrittlement, cracking and other phenomena under the influence of natural environmental factors such as long-term sun exposure, rainfall, and temperature changes, resulting in a decrease in waterproof performance, shortening of service life and increasing maintenance costs.

Method used

By precisely mixing raw material ingredients, a polymer modified asphalt waterproof material is developed, including asphalt, styrene-butadiene-styrene block copolymer modifier, random polypropylene, rubber powder, antioxidants, ultraviolet absorbers, compatible agents and fillers, and a specific preparation method is used to improve the weather resistance of the material.

Benefits of technology

Through the synergistic action of modifiers and antioxidants, this material significantly extends its service life, reduces the frequency and cost of waterproofing and maintenance of buildings, and further enhances the UV resistance and tensile strength through the addition of nanomaterials and fibers, and improves the weather resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529557A_ABST
    Figure CN119529557A_ABST
Patent Text Reader

Abstract

The invention relates to the field of waterproof materials, and discloses a polymer modified asphalt waterproof material and a preparation method thereof.The polymer modified asphalt waterproof material is prepared from 40%-50% of asphalt, 8%-12% of polymer modifier, 5%-8% of atactic polypropylene, 3%-5% of rubber powder, 0.5%-1% of antioxidant, 0.3%-0.5% of ultraviolet light absorber, 1%-2% of compatilizer and 15%-20% of filler, the polymer modifier is specifically a styrene-butadiene-styrene block copolymer, the antioxidant is specifically a hindered phenol antioxidant, the ultraviolet light absorber is specifically a benzotriazole ultraviolet light absorber, the filler is specifically a mixture of talcum powder and calcium carbonate, the talcum powder accounts for 60-70% of the total amount of the filler, and the calcium carbonate accounts for 10-30% of the total amount of the filler. And calcium carbonate accounts for 30%-40%. By adding the styrene-butadiene-styrene block copolymer modifier, the hindered phenol antioxidant and the benzotriazole ultraviolet light absorber, the service life is remarkably prolonged, the waterproof maintenance frequency and cost of a building are reduced, and a long-acting waterproof defense line is built for the building.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof materials, and in particular to a polymer modified asphalt waterproof material and a preparation method thereof. Background Art

[0002] In the construction industry, the performance of waterproof materials is directly related to the quality and service life of buildings. As a commonly used waterproof material, polymer modified asphalt waterproof material has been widely used in various construction projects.

[0003] Traditional asphalt waterproofing materials can meet basic waterproofing needs to a certain extent. However, with the continuous development of construction technology and the increasing complexity of environmental conditions, its performance has gradually exposed many deficiencies. In terms of weather resistance, traditional asphalt waterproofing materials are particularly poor. Due to the limitations of its composition and structure, it is prone to aging, embrittlement, cracking and other phenomena under the influence of long-term natural environmental factors such as sunlight, rain, and temperature changes. This will not only lead to a rapid decline in waterproofing performance, but also shorten the service life of waterproofing materials and increase the cost of maintenance and replacement. In the hot summer, high temperatures will make traditional asphalt waterproofing materials soften and flow, affecting their waterproofing effect; while in the cold winter, low temperatures will make them brittle and hard, and cracks will easily form, thus providing channels for water penetration. In addition, long-term exposure to ultraviolet rays will also destroy the molecular structure of traditional materials, further reducing their weather resistance.

[0004] In order to solve these problems, the development of a polymer modified asphalt waterproof material with excellent weather resistance and its efficient preparation method has become an important issue that needs to be urgently solved in the current field of building waterproofing. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a polymer modified asphalt waterproof material and a preparation method thereof, which solves the problem that although traditional asphalt waterproof materials can meet basic waterproofing needs, with the development of construction technology and complex environmental changes, they are limited by their component structure, have poor weather resistance, and are easily affected by natural environmental factors, resulting in aging, embrittlement, cracking and other problems, which affect the waterproofing effect, shorten the service life and increase the cost.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a polymer modified asphalt waterproof material, including 40%-50% asphalt, 8%-12% polymer modifier, 5%-8% random polypropylene, 3%-5% rubber powder, 0.5%-1% antioxidant, 0.3%-0.5% ultraviolet absorber, 1%-2% compatibilizer, and 15%-20% filler.

[0007] Preferably, the polymer modifier is specifically styrene-butadiene-styrene block copolymer.

[0008] Preferably, the antioxidant is a hindered phenol antioxidant.

[0009] Preferably, the ultraviolet absorber is a benzotriazole ultraviolet absorber.

[0010] Preferably, the filler is a mixture of talc and calcium carbonate, wherein the talc accounts for 60%-70% of the total amount of the filler, and the calcium carbonate accounts for 30%-40%.

[0011] A method for preparing a polymer modified asphalt waterproof material comprises the following steps: S1. placing asphalt in a reactor, controlling the reactor to heat up, and controlling the reactor to stir, thereby softening and removing impurities; S2. The rubber powder is sieved and then preheated using a heater to sieve the rubber powder; S3. Prepare fillers in proportion and sieve for later use; S5. Using a crusher to crush the polymer modifier and random polypropylene; S6. The asphalt in the reactor is heated, the preheated rubber powder is added, and the mixture is mixed and stirred; S7. The temperature in the reactor is raised, and a polymer modifier is added for mixing and stirring, the reaction is monitored, and the temperature is lowered after completion; S8. Lower the temperature of the reactor, add a compatibilizer and mix with stirring, and then add an antioxidant and a UV absorber to mix the mixture thoroughly; S9. Slowly add the filler to fully mix it with the mixture, and after mixing, reduce the stirring speed to exhaust; S10. The formed material is taken out along the inner wall of the reactor, and the material is extruded and formed using an extruder.

[0012] Preferably, in step S1, during the asphalt heating process, the temperature of the reactor is 130-140°C, the stirring speed is 300-400 rpm, and the stirring time is 20-30 minutes or 25-30 minutes.

[0013] Preferably, in step S7, during the mixing of the polymer modifier, the temperature of the reactor is 180-190° C., and the stirring speed is 800-1000 rpm.

[0014] Preferably, in step S8, the heating temperature of the compatibilizer is 80-120° C., and the stirring speed is 600-700 rpm for 5-8 minutes, and the stirring speed of the antioxidant and the ultraviolet absorber is 500-600 rpm for 3-5 minutes each.

[0015] Preferably, in step S9, the stirring and mixing speed during the filling material mixing process is 700-800 rpm for 10-15 minutes, and the stirring and mixing speed during the filling material exhaust process is 300-400 rpm for 5-8 minutes.

[0016] The present invention provides a polymer modified asphalt waterproof material and a preparation method thereof. It has the following beneficial effects: 1. The present invention builds a high-performance protective barrier by precisely blending raw materials. With an appropriate proportion of asphalt as the main body and a styrene-butadiene-styrene block copolymer modifier, the material is endowed with excellent flexibility, which can effectively buffer the deformation stress of the base layer and reduce the generation of cracks; the hindered phenol antioxidant and the benzotriazole ultraviolet absorber work synergistically to accurately snipe oxidation and ultraviolet damage, stabilize the material structure, significantly extend the service life, reduce the frequency and cost of building waterproof maintenance, and build a long-term waterproof defense line for the building.

[0017] 2. The present invention is adapted to different occasions by setting different embodiments. Embodiment 2 newly adds nano titanium dioxide, titanium dioxide and hindered amine light stabilizers. The strong combination of nano materials and light stabilizers greatly enhances the ability to resist ultraviolet rays, making the material "as stable as a mountain" under the scorching sun, and improving weather resistance; Embodiment 3 implants glass fiber, aramid fiber and carbon fiber to weave a strong tensile "network", which exponentially improves the tensile strength of the material, resists external pulling, and prevents cracking during use; Embodiment 4 adds polyether polyol, sodium dodecyl sulfate and Tween to accelerate the fusion of the components, greatly shorten the mixing time, soar in production efficiency, meet the needs of large-scale production, and can be accurately matched with different scene applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1: Please refer to the attached Figure 1The embodiment of the present invention provides a polymer modified asphalt waterproof material, including 40%-50% asphalt, 8%-12% polymer modifier, 5%-8% random polypropylene, 3%-5% rubber powder, 0.5%-1% antioxidant, 0.3%-0.5% ultraviolet absorber, 1%-2% compatibilizer, and 15%-20% filler; The polymer modifier is specifically a styrene-butadiene-styrene block copolymer; The antioxidant is specifically a hindered phenol antioxidant; The ultraviolet absorber is specifically a benzotriazole ultraviolet absorber; The filler is specifically a mixture of talcum powder and calcium carbonate, wherein the talcum powder accounts for 60%-70% of the total amount of the filler, and the calcium carbonate accounts for 30%-40%.

[0021] A method for preparing a polymer modified asphalt waterproof material comprises the following steps: S1. Place the asphalt in a reactor, heat to 130-140°C, stir at 300-400 rpm for 20-30 minutes to soften and remove impurities; S2. The rubber powder is sieved using a 80-100 mesh sieve, and then the sieved rubber powder is preheated using a heater for 10-15 minutes; S3. Prepare the filler in proportion and pass it through a 100-120 mesh sieve for later use; S5. Use a crusher to crush the polymer modifier and random polypropylene to a particle size of 2-5 mm; S6. The asphalt is heated to 160-170 ° C, the preheated rubber powder is added, and the stirring speed in the reactor is adjusted to 500-600 rpm, and the stirring time is 15-20 minutes; S7. The temperature in the reactor was raised to 180-190 ° C, a polymer modifier was added, and the speed was adjusted to 800-1000 rpm and stirred for 25-30 minutes, the reaction was monitored, and the temperature was lowered to 160-170 ° C after completion; S8. Lower the temperature of the reactor to 80-120 ° C, add a compatibilizer, and adjust the reactor speed to 600-700 rpm and stir for 5-8 minutes, then add an antioxidant and a UV absorber, adjust the reactor speed to 500-600 rpm and stir for 3-5 minutes each; S9. Slowly add filler and adjust the reactor speed to 700-800 rpm and stir for 10-15 minutes; then reduce to 300-400 rpm and stir for 5-8 minutes to exhaust; S10. The formed material is taken out along the inner wall of the reactor, and the material is extruded using an extruder, wherein the temperature of the extruder is 140-160° C. and the pressure is 3-5 MPa.

[0022] Example 1 Beneficial Effects: In this example, a specific proportion of polymer modifiers is used to enable the material to better adapt to the deformation of the base layer, reduce cracks caused by deformation of the base layer, and greatly enhance flexibility. The addition of hindered phenol antioxidants and benzotriazole ultraviolet absorbers effectively delays the oxidative aging process of the material, significantly reduces the damage of ultraviolet rays to the material, and greatly improves the weather resistance.

[0023] Embodiment 2: A polymer modified asphalt waterproof material, comprising 48% asphalt, 11% polymer modifier, 7% random polypropylene, 4.5% rubber powder, 0.9% antioxidant, 0.45% ultraviolet absorber, 1.8% compatibilizer, 18% filler, 2.5% nano titanium dioxide, 1.5% titanium dioxide, and 1.5% hindered amine light stabilizer.

[0024] Beneficial effects of Example 2: In this example, on the basis of Example 1, nano titanium dioxide, titanium dioxide and hindered amine light stabilizers are further added. Nano titanium dioxide can enhance the anti-ultraviolet performance, titanium dioxide can further enhance the anti-ultraviolet effect, and hindered amine light stabilizers can be used to enhance the weather resistance of the material, which significantly enhances the anti-ultraviolet performance of the material and greatly improves the weather resistance of the material.

[0025] Embodiment 3: A polymer modified asphalt waterproof material, comprising 43% asphalt, 9% polymer modifier, 6% random polypropylene, 3.5% rubber powder, 0.7% antioxidant, 0.35% ultraviolet absorber, 1.3% compatibilizer, 17% filler, 2.5% glass fiber, 1.5% aramid fiber, and 1.5% carbon fiber.

[0026] Embodiment 3 Beneficial effect: In this embodiment, on the basis of embodiment 1, glass fiber, aramid fiber and carbon fiber are further added, the tensile strength of the material is improved by glass fiber, the tensile performance is further enhanced by aramid fiber, and the mechanical properties of the material are optimized by carbon fiber, which significantly improves the tensile strength of the material and effectively reduces the risk of cracking of the material during use. Embodiment 4: A polymer modified asphalt waterproof material, comprising 45% asphalt, 10% polymer modifier, 6.5% random polypropylene, 4% rubber powder, 0.8% antioxidant, 0.4% ultraviolet absorber, 1.5% compatibilizer, 16% filler, 1.5% polyether polyol, 1.5% sodium lauryl sulfate, and 1.5% Tween.

[0027] Beneficial effect of Example 4: In this example, based on Example 1, polyether polyol, sodium lauryl sulfate and Tween are further added. Polyether polyol is used to accelerate the mixing speed between the components, sodium lauryl sulfate is used to promote mixing, and Tween is used to improve the uniformity of mixing, which significantly accelerates the mixing speed between the components and improves production efficiency.

[0028] Comparative experiment: 1. Weathering performance comparison test: Experimental design: Five specimens of the polymer modified asphalt waterproof material of Example 1, Example 2, Example 3, and Example 4 with the same specifications (20 cm×20 cm×0.5 cm) were prepared.

[0029] The specimens were placed in an accelerated aging test chamber simulating an outdoor environment. The test conditions were set as follows: UV radiation intensity 500W / m², temperature cycle range -20℃-60℃, humidity 40%-80%, and test period 1000 hours.

[0030] The test specimens were taken out every 200 hours, and the color change on the surface of the specimens was measured using a colorimeter (expressed as ΔE value; the larger the ΔE value, the more obvious the color change and the worse the weather resistance). At the same time, the tensile strength retention rate of the test specimens was tested using a universal material testing machine (the higher the tensile strength retention rate, the better the weather resistance).

[0031] Experimental results: Example 1: After 1000 hours of testing, the average ΔE value of the test piece was 12, and the tensile strength retention rate was 70%. Although it has a certain weather resistance basis, compared with other examples, it lacks strong anti-ultraviolet components such as nano titanium dioxide, and the aging performance is relatively obvious.

[0032] Example 2: The average ΔE value of the test piece is only 8, and the tensile strength retention rate is 85%. Nano-titanium dioxide, titanium dioxide and hindered amine light stabilizers work together to effectively block ultraviolet erosion and inhibit photooxidation reactions, making its weather resistance far superior to other groups, and maintaining good color and mechanical properties.

[0033] Example 3: The average ΔE value is 10, and the tensile strength retention rate is 75%. Fiber additives focus on improving mechanical properties, and have limited auxiliary effects on UV resistance and weather resistance, and color change and strength loss are at an intermediate level.

[0034] Example 4: The average ΔE value is 11, and the tensile strength retention rate is 72%. The additives such as polyether polyols mainly accelerate mixing, and do not focus on improving weather resistance. The degree of environmental influence on the test piece is similar to that of Example 1.

[0035] 2. Tensile strength comparison test: Experimental design: Dumbbell-shaped standard test pieces were made, and 4 test pieces were prepared for each group of example materials, and the sizes met the requirements of national standards (such as GB / T528-2009).

[0036] The specimen was fixed on a universal material testing machine and subjected to a tensile test at a tensile speed of 500 mm / min until the specimen broke. The maximum tensile force at the time of fracture was recorded and the tensile strength was calculated (tensile strength = maximum tensile force ÷ cross-sectional area of ​​the specimen).

[0037] Experimental results: Example 1: The average tensile strength is 3.5 MPa. The basic formula focuses on flexibility and weather resistance, and high-strength fiber reinforcement is not added. It relies on polymer modifiers and rubber powder to maintain a certain toughness, but the tensile strength is limited.

[0038] Example 2: The average tensile strength is 4.2 MPa. Nano titanium dioxide and other ingredients improve weather resistance and have a certain reinforcing effect, but they are not specifically tensile reinforcement, and the improvement is smaller than that of Example 3.

[0039] Example 3: Average tensile strength reaches 6.0 MPa. The composite effect of glass fiber, aramid fiber and carbon fiber builds a strong fiber network, significantly improves the material's tensile bearing capacity, effectively disperses stress, and makes the tensile performance far superior to other examples.

[0040] Example 4: The average tensile strength is 4.0 MPa. Additives such as polyether polyols assist in mixing, but do not substantially improve the intrinsic tensile strength of the material, and the mechanical properties remain at the basic level.

[0041] 3. Mixing speed comparison experiment: Experimental design: In the laboratory, a production environment was simulated, a high-speed stirring kettle of the same specification (volume 50 L) was equipped, and the raw materials corresponding to the proportions of each embodiment were put into it, and each group of experiments was repeated 3 times.

[0042] From the beginning of stirring, use an online viscometer to monitor the viscosity change of the material in real time. The mixing endpoint is when the material reaches uniformity and stability and the viscosity fluctuation is less than 5%, and the required time is recorded.

[0043] Experimental results: Example 1: The average mixing time is 60 minutes. Conventional materials rely on mechanical stirring to blend, without special mixing agents, and it takes a long time for each component to disperse, especially the polymer modifier disperses slowly.

[0044] Example 2: The average mixing time is 55 minutes. Powdered additives such as nano-titanium dioxide interfere with mixing to a certain extent. Although they have good dispersibility, they do not accelerate the overall process and are slightly faster than Example 1.

[0045] Example 3: The average mixing time is 58 minutes. Fiber additives are easy to tangle, which increases the difficulty of stirring and delays the uniform mixing. The time is close to that of Example 1.

[0046] Example 4: The average mixing time is 45 minutes. The polyether polyol reduces the surface tension of the system, the sodium dodecyl sulfate emulsifies and disperses, and the Tween assists in stirring, which synergistically greatly speeds up the mixing and significantly saves time.

[0047] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A polymer modified asphalt waterproof material, characterized in that: Including asphalt 40%-50%, polymer modifier 8%-12%, random polypropylene 5%-8%, rubber powder 3%-5%, antioxidant 0.5%-1%, UV absorber 0.3%-0.5%, compatibilizer 1%-2%, filler 15%-20%.

2. A polymer modified asphalt waterproof material according to claim 1, characterized in that: The polymer modifier is specifically a styrene-butadiene-styrene block copolymer.

3. The polymer modified asphalt waterproof material according to claim 1, characterized in that: The antioxidant is specifically a hindered phenol antioxidant.

4. The polymer modified asphalt waterproof material according to claim 1, characterized in that: The ultraviolet absorber is specifically a benzotriazole ultraviolet absorber.

5. The polymer modified asphalt waterproof material according to claim 1, characterized in that: The filler is specifically a mixture of talcum powder and calcium carbonate, wherein the talcum powder accounts for 60%-70% of the total amount of the filler, and the calcium carbonate accounts for 30%-40%.

6. A method for preparing a polymer modified asphalt waterproof material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. placing the asphalt in a reactor, controlling the reactor to heat up, and controlling the reactor to stir, thereby softening and removing impurities; S2. The rubber powder is sieved and then preheated using a heater to sieve the rubber powder; S3. Prepare the filler materials in proportion and sieve them for later use; S5. Using a crusher to crush the polymer modifier and random polypropylene; S6. The asphalt in the reactor is heated, the preheated rubber powder is added, and the mixture is mixed and stirred; S7. The temperature in the reactor is raised, and a polymer modifier is added for mixing and stirring, the reaction is monitored, and the temperature is lowered after completion; S8. Lower the temperature of the reactor, add a compatibilizer and mix with stirring, and then add an antioxidant and a UV absorber to mix the mixture thoroughly; S9. Slowly add the filler to fully mix it with the mixture, and after mixing, reduce the stirring speed to exhaust; S10. The formed material is taken out along the inner wall of the reactor, and the material is extruded and formed using an extruder.

7. The method for preparing a polymer modified asphalt waterproof material according to claim 6, characterized in that: In the step S1, during the asphalt heating process, the temperature of the reactor is 130-140°C, the stirring speed is 300-400 rpm, and the stirring time is 20-30 minutes or 25-30 minutes.

8. The method for preparing a polymer modified asphalt waterproof material according to claim 6, characterized in that: In the step S7, during the mixing process of the polymer modifier, the temperature of the reactor is 180-190° C., and the stirring speed is 800-1000 rpm.

9. The method for preparing a polymer modified asphalt waterproof material according to claim 6, characterized in that: In the step S8, the heating temperature of the compatibilizer is 80-120° C., and the stirring speed is 600-700 rpm for 5-8 minutes, and the stirring speed of the antioxidant and the ultraviolet absorber is 500-600 rpm for 3-5 minutes each.

10. The method for preparing a polymer modified asphalt waterproof material according to claim 6, characterized in that: In the step S9, the stirring and mixing speed during the filling material mixing process is 700-800 rpm for 10-15 minutes, and the stirring and mixing speed during the filling material exhaust process is 300-400 rpm for 5-8 minutes.

Citation Information

Cited By

  • Waterproof coiled material with good anti-aging performance and production method thereof

    CN120921765A